USING SOCIOGRAM METHOD TO DEVELOP WRITING SKILL TO THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 2 OKU - Novarita Novarita (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
There were manv reasons why the students consider writing skill is a difficult thing. First. the students' writing is not comprehensible, because the content of the composition is not relevant to the topic, the ideas are not clearly stated the ideas, and sentences are not well organized. Second. there are many errors in vocabulary, grammar, and spelling. Another reason is the students' difficult in connecting the characters in the story of text that they write. Students are also difficulties in arranging the words according to the storyline and the role of every character in the story of text. Sociogram method was focus in social relationships between characters and the place. That was why the researcher chooses the title "Using Sociogram Method to Develop Writing Skill to the Eleventh Grade Students of SMA Negeri 2 OKU" for her research design. The main objective of this study was to find out whether or not was there the significantly effective using sociogram method for develop writing skill to the eleventh grade students of SMA Negeri 2 OKU. The researcher used the pre-experimental method. The population was students of SMA Negeri 2 OKU in academic year 2012/2013. The total number of population was 139 students. The sample of this study was 36 students. They were taken by using cluster random sampling technique and it got one class as sample of the research. The data were collected through written test in form of essay test. The researcher used matched t-test for analyzing the data. The result of the data analysis showed that there was significant difference of students' writing skill between the result of pre test and post-test in research process. There was difference in the result of Mean. Based on the result of the data analysis the researcher was found that the gained t of sample class (t0) 5.45 in the level of 5% and df: 34 (35-1) and t-table was 2.03 or to> T table. It meant that the Altemative hypothesis is accepted and null hypothesis is rejected. This indicates there is effective to develop students' writing skill through sociogram method.